Unfuck your addiction : using science to free yourself from harmful reliance on substances, habits, and out of control behaviors - Harper, Faith G. (Microcosm Publishing, 2023)
"We have almost all been addicted to something at some point, or had a habit spiral out of control. But what does that mean? What exactly are addictions and out of control behaviors, why do we get caught up in them, and how do we get our lives back? Bestselling author Dr. Faith Harper and addictions counselor Joe Green join forces to help those of us struggling (or supporting others) with problematic use of alcohol, drugs, gambling, work, food, sex, shopping, screens, gaming, self-harm, or anything else where we've crossed a line. Their perspective is down to earth, realistic, and refreshing. You'll learn about the brain science behind addiction, how to tell if something is a problem or about to become one, how to find your way out of unhealthy behaviors, and how to avoid passing them down to the next generation. No matter what paths you've taken in life, you can absolutely learn to fulfill your needs in ways that are healthy for yourself and the people around you"--